Comparative analysis of dominant gut microbiota in Inflammatory Bowel Disease patients and healthy individuals: A case-control study - Alireza Ahmadi; Ebrahim Kouhsari; Shabnam Razavi; Nima Mohamadzadeh; Sima Besharat; Mohammad Ali Vakili; Taghi Amiriani (New Microbes and New Infections)
Background: Chronic inflammation in the gut might be linked to microbiota dysbiosis. Objective: This study aimed to investigate alterations in the gut microbiota composition of adult IBD patients compared to healthy controls. Methods: This case-control study investigated the relationship between faecal microbiota composition and IBD in adults. Real-time qPCR analysis using bacterial 16S rRNA gene quantified the abundance of six key bacterial groups (Firmicutes, Lactobacillus spp., Bifidobacterium spp., Fusobacterium spp., Bacteroides fragilis, and Faecalibacterium prausnitzii) in faecal samples from 30 IBD patients (13 Crohn's disease, 17 ulcerative colitis) and 30 healthy controls. A correlation matrix was employed to assess relationships between these bacteria. Results: Real-time qPCR revealed significant differences (p-value <0.05) in the abundance of several bacterial groups between IBD patients and healthy controls. Firmicutes, Fusobacterium spp., and B. fragilis were significantly more abundant (p-value <0.05) in IBD patients compared to controls. Conversely, Lactobacillus spp. and F. prausnitzii were both significantly less abundant (p-value <0.05) in IBD patients. While some bacterial groups exhibited trends toward higher abundance in either CD or UC patients, these differences were not statistically significant (p-value >0.111). The correlation matrix analysis revealed specific co-occurrence patterns: Bacteroides showed a strong negative correlation with Prevotella, more abundant in healthy controls, suggesting a shift in dominance in IBD patients. Lactobacillus spp. and F. prausnitzii exhibited a positive correlation in healthy individuals, indicating their potential cooperative role in maintaining gut homeostasis. Conclusion: This study identified significant alterations in gut microbiota composition in adult IBD patients compared to healthy controls, with notable differences in the abundance of specific bacterial groups. These findings suggest that gut microbiota dysbiosis may play a critical role in IBD pathogenesis. The identification of specific bacterial imbalances provides a foundation for developing microbiota-based therapies, such as probiotics, prebiotics, and fecal microbiota transplantation, as potential interventions for restoring microbial balance and mitigating disease progression. Further research is needed to translate these insights into targeted therapeutic strategies and to explore their effectiveness in clinical settings.